Literatur Review: Efektivitas Pemberian Aromaterapi Peppermint Terhadap Pengurangan Mual dan Muntah pada Ibu Hamil Trimester I: Literature Review: The Effectiveness of Administering Peppermint Aromatherapy on Reducing Nausea and Vomiting in First Trimester Pregnant Women - Maria Oktavia; Ika Avrilina Haryono; Susanti Suhartati (Jurnal Surya Medika (JSM), 2023)
Background: Nausea and vomiting of pregnancy or often referred to as "morning sickness" is a symptom of nausea which is usually accompanied by vomiting and is physiological due to pregnancy, which generally occurs in the first trimester. If nausea and vomiting occurs and it is not treated immediately, it can cause more severe symptoms of nausea and vomiting that will occur early in pregnancy so that it can cause dehydration, electrolyte disturbances or nutritional deficits or what is known as hyperemesis gravidarum. Purpose: This study aims to determine the effectiveness of Peppermint Aromatherapy for Reducing Nausea and Vomiting in Trimester I Pregnant Women. Methods: This study uses a literature review study approach using several journal sources or articles that are selected based on predetermined criteria. The results of 11 types of literature review, there are 9 journals saying peppermint aromatherapy can reduce nausea and vomiting, 2 journals say that peppermint aromatherapy provides less effectiveness in reducing nausea and vomiting. Conclusion: The effectiveness of peppermint aromatherapy in dealing with cases of nausea and vomiting in pregnant women so that there is a reduction in nausea and vomiting in trimester I pregnant women.